Analysis on solar energy powered cooling system based on desiccant coated heat exchanger using metal-organic framework. (15th June 2019) - Xu, F.; Bian, Z.F.; Ge, T.S.; Dai, Y.J.; Wang, C.H.; Kawi, S.
Abstract: The solar powered cooling system based on desiccant coated heat exchanger (DCHE) is an alternative to traditional vapor compression cooling system (VCCS) due to its energy-saving and eco-friendliness. To obtain improved performance, high-porosity Metal-Organic Framework (MOF) is introduced as desiccant. In our study, Cu-BTC (HKUST-1) was fabricated and certified with high purity and good crystallization by X-ray diffraction (XRD). N2 isotherm adsorption-desorption properties of MOF were investigated. Results show that MOF has co-existence of micropores and mesopores with relatively large specific surface area and pore volume. Water vapor isotherm adsorption of MOF and type B silica gel (SGB) was conducted. Isotherms indicate that moisture uptake of MOF is higher than that of SGB at low relative humidity. A dynamic mathematical model of this system was established. The solar performance was evaluated firstly. Results suggest that solar collector can provide 52.5–80.4 °C hot water from 9:00 to 19:00. Then the simulation was conducted under American Air-conditioning and Refrigeration Institute (ARI) summer and Shanghai August conditions. Results exhibit that MOF coated heat exchanger (MCHE) has more significant enhancement of dehumidification performance than SGB coated heat exchanger (SCHE) with increased regeneration temperature and MCHE is more suitable for application under ARI summer condition. Highlights: MOF fabricated has high purity and good crystallization. Moisture uptake of the MOF is relatively large at low relative humidity. Dehumidification capacity of MCHE is more sensitive to regeneration temperature. MCHE is more suitable for ARI summer condition. Shorting cycle time can improve dehumidification performance of MCHE.